Fabrication of a High Wear Resistance AA7075/AL2O3 Composites Via Liquid Metallurgy Process - R. Sivaraman; Abduladheem Turki Jalil; Surendar Aravindhan; Zhao Nan; M. Heydari Vini; S. Daneshmand (International Journal of Applied Mechanics and Engineering, 2022)
In the present study, AA7075/Al2O3 composites have been fabricated via liquid metallurgy process. AA7075 alloy and Al2O3 particles were taken as the base matrix and reinforcements, respectively. Then, contents of 3 and 6 wt. % of Al2O3 subdivisions were added into the AA7075 matrix. To improve wettability and distribution, reinforcement particles were pre-heated to a temperature of 550°C for each composite sample. A hardened EN32 steel disc as the counter face was used to evaluate the wear rate pin-on-disc. The results showed that the wear rate of the AA/Al2O3 composites was smaller than that of the monolithic AA7075 samples. Finally, the worn surfaces of samples were investigated by SEM.